THE EFFECT OF FINANCIAL LITERATURE, HUMAN RESOURCES COMPETENCE AND THE UTILIZATION OF INFORMATION TECHNOLOGY ON FINANCIAL MANAGEMENT IN MSMES IN LHOKSEUMAWE CITY - F, Farhani; Raza, Hendra; N, Naz'aina (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the priorities in national economic development. MSMEs provide the largest contribution to the trade sector as much as 46.17% with a workforce distribution of 31.81% which is one of the economic drivers of the people and supporters of the Indonesian economy. In business, decision making must be rational and based on available information. This shows that the importance of the level of knowledge related to information as well as qualified human resources to make good decisions. This research design is descriptive and quantitative. This research was conducted at Micro, Small and Medium Enterprises which are active in Lhokseumawe City. Statistical analysis shows that financial literacy, human resource competence and information technology have a significant effect on the financial management of Micro, Small and Medium Enterprises in Lhokseumawe City. The results of this study provide useful information and valuable insights for MSMEs and can find out the magnitude of the role of financial literacy, human resource competence, technology and financial management in maintaining or developing a business, so as to increase innovation and be proactive in managing MSMEs so that they are able to face competition.